2004
DOI: 10.1002/ptr.1459
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic effect of stigmast‐4‐en‐3‐one and its corresponding alcohol from the bark of Anacardium occidentale (cashew)

Abstract: Intravenous administration of the hexane extract of the bark of Anacardium occidentale (cashew) in normal, healthy dogs produced a significant lowering of the blood glucose levels. Pursuit of the hypoglycaemic principle(s) in the hexane extract resulted in the isolation and characterization of two compounds, stigmast-4-en-3-ol (1) and stigmast-4-en-3-one (2). These compounds were purified by chromatographic methods and the structures were characterized by spectroscopic methods. Both compounds produced signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 10 publications
1
38
1
Order By: Relevance
“…Reports showed that the aqueous, alcoholic and hexane extracts from the barks and leaves of A. occidentale had hypoglycemic effects (Ojewole, 2003;Alexander-Lindo et al, 2004;Sokeng et al, 2001;Kamtchouing et al, 1998). In the present work we showed that the ethanolic extract of the inner-bark of A. occidentale reduced the serum glucose level in diabetic rats but to our astonishment, the values did not return to those of normal controls (Table 3).…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Reports showed that the aqueous, alcoholic and hexane extracts from the barks and leaves of A. occidentale had hypoglycemic effects (Ojewole, 2003;Alexander-Lindo et al, 2004;Sokeng et al, 2001;Kamtchouing et al, 1998). In the present work we showed that the ethanolic extract of the inner-bark of A. occidentale reduced the serum glucose level in diabetic rats but to our astonishment, the values did not return to those of normal controls (Table 3).…”
Section: Resultscontrasting
confidence: 48%
“…(Kamtchouing et al, 1998;Sokeng et al, 2001;Alexander-Lindo et al, 2004;Ojewole, 2003;Olatunji et al, 2005;Leonard et al, 2006). However, investigations carried out specifically on the inner-soft bark extract of A. occidentale as a separate tissue are near to none.…”
Section: Introductionmentioning
confidence: 99%
“…The highest percentage of 9, 19-cyclolanost-24-en-3-ol was observed in Golden Delicious, 4.8 6 0.6% as compared to other varieties. The hypoglycaemic effects of stigmast-4-en-3-one have been reported (Alexander-Lindo et al, 2004). The highest level of stigmast-4-en-3-one was observed in Pyrus Malus, 4.6 6 0.6% as compared to the other varieties, which showed relatively lower amounts of Stigmast-4-en-3-one (, 4.00%).…”
Section: Fatty Acid Compositionmentioning
confidence: 94%
“…Otherwise, the inhibition of the microorganism, S. mutans and the formation of its biofilm open the door for its application in dental caries (Furtado et al, 2014). The aqueous extract of cashew has hypoglycemic activity (Alexander-Lindo et al, 2004).…”
Section: A Occidentale and Its Biological Rolesmentioning
confidence: 99%